Rancang Bangun Smart Pot Berbasis Internet Of Things (IoT) - Armando Mendoza Putra; Joni Eka Candra; Luki Hernando (JURNAL QUANCOM: QUANTUM COMPUTER JURNAL, 2026)
The Internet of Things (IoT) has the potential to transform the agriculture industry by increasing the efficiency of using resources such as water and fertilizer. Common problems in agriculture, such as water scarcity or excess, can be solved with an automated system that measures soil moisture and adjusts watering according to crop needs. In this study, researchers proposed an automated monitoring and watering system utilizing the Blynk platform and Internet of Things (IoT) technology. This system allows real-time monitoring of plant conditions through Capacitive soil sensor and DHT 11 sensor. The collected data will be processed by ESP8266 NodeMCU to regulate the automatic watering process with smart irrigation that is automatically adjusted to the needs of plants. Through the Blynk app, users can monitor and control the system remotely, improving efficiency and optimal care for plants. Thus, this system provides a solution for those who have limited time or unwillingness to care for plants conventionally.